(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
Complex field experiments were carried out in Agricultural research institute in 1969. The field trials included five different crop rotation systems. In each 6-field rotation system the specific percentage of cereals (%) varied from 50 to 100%, perennial grass (clover+ timothy) - 16.7 to 33.3%. The highest winter rye yields were obtained from crop rotation systems with cereal proportion up to 66%. Including buckwheat in the crop rotation winter rye cultivation is highly productive in crop rotation systems with cereal proportion even up to 83%. Yield of winter rye in long-term monocultural sowings decreases even up to 0.74h-1. Winter ryetreatment with herbicide Grodil increases its yield up to 0.40 ha'1. Foreplants of barley according to their good influence on barley yield (descending): buckwheat, oats, winter lye. Barley yield in long-term monocultural sowings decreases for up to 1.17 t ha-1.Oats in crop rotation systems with cereal proportion up to 83% had very low yield amount alterations after different foreplants. Essential oat yield decreasement was noticed in perennial monocultural sowings. The best foreplants for spring wheat are buckwheat and lupine. The highest yield of buckwheat is get from monocultural sowings, but using potatoes as buckwheat foreplant gives essential yield decreasement. Distribution of perennial weeds, especially quickgrass, is 7,4 times more in crop rotation systems with high cereal proportion than in systems where also buckwheat and potatoes are cultivated. Treatment of herbicides and fungicides is more effective in monocultural sowings than in crop rotational systems, however increasement of crop yield after pesticide treatment is less remarkable than if we follow right crop rotation and choose optimal foreplants for each culture. Latest results from years 2002 to 2004 are shown in this article and are considered to be an addition to previous publications.